Lack of antibodies against seasonal coronavirus OC43 nucleocapsid protein identifies patients at risk of critical COVID-19 - Dugas, Martin; Grote-Westrick, Tanja; Merle, Uta; Fontenay, Michaela; Kremer, Andreas E.; Hanses, Frank; Vollenberg, Richard; Lorentzen, Eva; Tiwari-Heckler, Shilpa; Duchemin, Jérôme; Ellouze, Syrine; Vetter, Marcel; et al. (Clinical and diagnostic virology, 2021)
Background - The vast majority of COVID-19 patients experience a mild disease. However, a minority suffers from critical disease with substantial morbidity and mortality. - Objectives - To identify individuals at risk of critical COVID-19, the relevance of a seroreactivity against seasonal human coronaviruses was analyzed. - Methods - We conducted a multi-center non-interventional study comprising 296 patients with confirmed SARS-CoV-2 infections from four tertiary care referral centers in Germany and France. The ICU group comprised more males, whereas the outpatient group contained a higher percentage of females. For each patient, the serum or plasma sample obtained closest after symptom onset was examined by immunoblot regarding IgG antibodies against the nucleocapsid protein (NP) of HCoV 229E, NL63, OC43 and HKU1. - Results - Median age was 60 years (range 18-96). Patients with critical disease (n=106) had significantly lower levels of anti-HCoV OC43 nucleocapsid protein (NP)-specific antibodies compared to other COVID-19 inpatients (p=0.007). In multivariate analysis (adjusted for age, sex and BMI), OC43 negative inpatients had an increased risk of critical disease (adjusted odds ratio (AOR) 2.68 [95% CI 1.09 - 7.05]), higher than the risk by increased age or BMI, and lower than the risk by male sex. A risk stratification based on sex and OC43 serostatus was derived from this analysis. - Conclusions - Our results suggest that prior infections with seasonal human coronaviruses can protect against a severe course of COVID-19. Therefore, anti-OC43 antibodies should be measured for COVID-19 inpatients and considered as part of the risk assessment for each patient. Hence, we expect individuals tested negative for anti-OC43 antibodies to particularly benefit from vaccination against SARS-CoV-2, especially with other risk factors prevailing.